Battery and Ultra-Capacitor Based Hybrid Energy Storage System Utilizing a Multi-Input DC-DC Buck-Boost Converter - Mahmud, Monowar; Abedin, Tarek; Mostofa, Kazi Zehad; Rahman, Atiqur; Basher, Mohammad Khairul; Nur-E-Alam, Mohammad (Journal of Graphic Era University, 2025)
Hybrid power systems have evolved into a vital component of contemporary power networks, finding application in various domains ranging from automotive to small-scale off-grid setups. Their purpose is to optimize the utilization of diverse energy sources. This study delves into the efficacy of integrating ultra-capacitors and batteries synergistically. Employing a multi-input converter to drive a variable DC load, the aim is to minimize losses and expenses. In the proposed configuration, a single inductor is utilized, facilitating the integration of a variable array of distributed energy sources. Notably, this converter expedites ultra-capacitor (UC) charging by offering a low inductance pathway, distinguishing it from conventional multi-input DC-DC converters. This proposed topology is bidirectional and adaptable to accommodate varying numbers of energy sources. The obtained numerical results reveal the converter’s effectiveness in stabilizing output voltage and current, making it suitable for multiple applications like electric vehicles, fuel cell systems, and renewable energy integration. Additionally, in the proposed topology, the results showed that it could charge a 2000F UC from a 300V source from 40% to 100% in just 400s and from a 150V battery from 20% to over 90% in just 200s due to the single inductor present in the charging path. Moreover, the load voltages are below 2% in all operational modes when either one or two sources are driving the load. Future research may focus on refining control algorithms to further enhance system efficiency and expand its applicability across different sectors.